De la perception du mouvement dans le sémantisme du verbe tomber et de ses correspondants polonais - Cholewa, Joanna (Neophilologica, 2015)
The French verb tomber can be translated into Polish as paść / padać and its derivatives formed with various prefixes, which denote the path of motion (semantic features of vertical orientation and downward direction are included in the base paść / padać). In this paper, we discuss four meanings of the verb tomber extracted from the dictionnary Les Verbes Français (01: ‘choir, chuter’, 05: ‘se détacher’, 06: ‘se défaire’, 28: ‘survenir sur’) and their Polish equivalents. We provide a comparison which shows differences of the perception of motion by the French and Polish language users.